First demonstration of the FLASH effect with ultrahigh dose rate high-energy X-rays. (January 2022) - Gao, Feng; Yang, Yiwei; Zhu, Hongyu; Wang, Jianxin; Xiao, Dexin; Zhou, Zheng; Dai, Tangzhi; Zhang, Yu; Feng, Gang; Li, Jie; Lin, Binwei; Xie, Gang; et al.
Highlights: The generation of High energy X-ray FLASH by the PARTER system and its physical properties were confirmed. This study reports the first demonstration of the FLASH effect triggered by high energy X-rays on a platform called PARTER. The study provides a basis for future scientific research and clinical application of HEX in FLASH radiotherapy. Abstract: Purpose: This study aimed to evaluate whether high-energy X-rays (HEXs) of the PARTER (platform for advanced radiotherapy research) platform built on CTFEL (Chengdu THz Free Electron Laser facility) can produce ultrahigh dose rate (FLASH) X-rays and trigger the FLASH effect. Materials and methods: EBT3 radiochromic film and fast current transformer (FCT) devices were used to measure absolute dose and pulsed beam current of HEXs. Subcutaneous tumor-bearing mice and healthy mice were treated with sham, FLASH, and conventional dose rate radiotherapy (CONV), respectively to observe the tumor control efficiency and normal tissue damage. Results: The maximum dose rate of HEXs of PARTER was up to over 1000 Gy/s. Tumor-bearing mice experiment showed a good result on tumor control ( p < 0.0001) and significant difference in survival curves ( p < 0.005) among the three groups. In the thorax-irradiated healthy mice experiment, there was a significant difference ( p = 0.038) in survival among the three groups, with the risk of death decreased by 81% in the FLASH group compared to that in the CONV group. The survival time of healthy mice irradiated in the abdomen in the FLASH group was undoubtedly higher (62.5% of mice were still alive when we stopped observation) than that in the CONV group (7 days). Conclusion: This study confirmed that HEXs of the PARTER system can produce ultrahigh dose rate X-rays and trigger a FLASH effect, which provides a basis for future scientific research and clinical application of HEX in FLASH radiotherapy.